BIOTECHNICAL POTENTIAL OF PASPALUM SUBMITTED TO SIMPLE SUPERPHOSPHATE DOSES AND MOISTURE CONTENT - Holanda, Francisco Sandro Rodrigues; Lino, Janisson Bispo; Santos, Maria Hosana; Garcez, Tiago Barreto; Araújo Filho, Renisson Neponuceno (Scientia Agraria, 2017)
The objective of this study was to evaluate the development of Paspalum grass millegrana Schrad propagated through seeds and tillers, subjected to different levels of water and phosphorus to be used in erosion control on slopes. The experimental trial was conducted in greenhouse with propagation of tillers and seeds of Paspalum grass, at the Federal University of Sergipe, São Cristóvão, Brazil, in a completely randomized design with sixteen treatments and four replications, arranged in a factorial scheme corresponding to (0, 100, 200, 300 and 400 mg kg-1), two water contents in the soil (60% and 100% of total pore volume) filled with water and two types of propagation (tillers and seeds). Plants were harvested at the end of four months of conducting the experiment and evaluated the following variables: number of tillers (NT), number of inflorescences (NI), Shoot Length (SL), Root Length (RL), Shoot Dry Weight (SDW) and Root Dry Weight (RDW). The phosphorus and water levels interacted positively with the variables studied and showed that this grass, presented biotech important features like good tillering, and the consequent formation of dense aerial biomass and root required for slope protection against erosion. The Paspalum millegrana species showed a better development among the variables analyzed under conditions of less water availability with 60% VTP and the best responses of the simple superphosphate dosages were between 200 and 300 mg kg-1.